The faces of justice and state authority : a comparative approach to the legal process - Damaška, Mirjan R., 1931- (Yale University Press, 1986)
A leading legal scholar provides a highly original comparative analysis of how justice is administered in legal systems around the world and of the profound and often puzzling changes taking place in civil and criminal procedure. Constructing a conceptual framework of the legal process based on the link between politics and justice, Mirjan R. Damaska provides a new perspective that enables disparate procedural features to emerge as fascinating recognizable patterns.--